Placements and influences on woodcarvings of traditional Malay houses in Negeri Sembilan - Nurdiyana Zainal Abidin, 1987- author; Raja Nafida Raja Shahminan, supervisor; Fakulti Alam Bina (2014)
Thesis (Sarjana Senibina) - Universiti Teknologi Malaysia, 2014